A First Y-Chromosomal Haplotype Network to Investigate Male-Driven Population Dynamics in Domestic and Wild Bactrian Camels - Felkel, Sabine; Wallner, Barbara; Chuluunbat, Battsesteg; Yadamsuren, Adiya; Faye, Bernard; Brem, Gottfried; Walzer, Chris; Burger, Pamela A. (Frontiers in Genetics, 2019)
Polymorphic markers on the male-specific part of the Y chromosome (MSY) provide useful information for tracking male genealogies. While maternal lineages are well studied in Old World camelids using mitochondrial DNA, the lack of Y-chromosomal references hampers the analysis of male-driven demographics. Recently, a shotgun assembly of the horse MSY was generated based on short read next generation sequencing data. The haplotype network resulting from single copy MSY variants using the assembly as a reference revealed sufficient resolution to trace individual male lines in this species. In a similar approach we generated a 3.8 Mbp sized assembly of the MSY of Camelus bactrianus. The camel MSY assembly was used as a reference for variant calling using short read data from eight Old World camelid individuals. Based on 596 single nucleotide variants we revealed a Y-phylogenetic network with seven haplotypes. Wild and domestic Bactrian camels were clearly separated into two different haplogroups with an estimated divergence time of 26,999 ± 2,268 years. Unexpectedly, one wild camel clustered into the domestic Bactrian camels’ haplogroup. The observation of a domestic paternal lineage within the wild camel population is concerning in view of the importance to conserve the genetic integrity of these highly endangered species in their natural habitat.